2018
DOI: 10.1177/0269881118756245
|View full text |Cite
|
Sign up to set email alerts
|

Propranolol for treating emotional, behavioural, autonomic dysregulation in children and adolescents with autism spectrum disorders

Abstract: This review indicates that propranolol holds promise for EBAD and cognitive performance in ASD. Given the lack of good quality clinical trials, randomised controlled trials are warranted to explore the efficacy of propranolol in managing EBAD in ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 90 publications
(167 reference statements)
0
29
0
Order By: Relevance
“…Therefore, it can be useful for treating disorders concerning to emotional and behavioral deficits caused by hyperarousal. Sixteen reports are found in a review about the use of propranolol in ASD ( Sagar-Ouriaghli et al, 2018 ). The results from the eight single-dose clinical trials led to significant improvements in cognitive performance, improvement in semantic networks and functional connectivity.…”
Section: Main Articlementioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can be useful for treating disorders concerning to emotional and behavioral deficits caused by hyperarousal. Sixteen reports are found in a review about the use of propranolol in ASD ( Sagar-Ouriaghli et al, 2018 ). The results from the eight single-dose clinical trials led to significant improvements in cognitive performance, improvement in semantic networks and functional connectivity.…”
Section: Main Articlementioning
confidence: 99%
“…The remaining eight single case reports and case series showed improvements in anxiety, aggressive, self-injurious and hypersexual behaviors. In no study a negative observation has been reported so far for the treatment with this kind of beta-blocker apart from high dose treatment that caused hypotension ( Sagar-Ouriaghli et al, 2018 ). This can be seen as a treatable side effect.…”
Section: Main Articlementioning
confidence: 99%
“…The use of propranolol is also frequently prescribed to address hyperarousal and social anxiety. Given that the atypical pupillary response co-occurs with respiratory sinus arrhythmia and externalizing behaviors, propranolol has had positive outcomes for addressing these physical indicators of anxiety associated with ASD and for improving functional neural connectivity during cognitive tasks [ 95 , 96 , 97 ].…”
Section: Pupillary Response Modulation Of the Lc-ne System And mentioning
confidence: 99%
“…28,29 Effects of beta-blockers in reducing autism-related emotional and behavioral dysregulation were also reported in a series of case studies. 30,31 Additionally, there are studies exploring the effects of propranolol on functional connectivity. 32,33 To date, few studies have aimed to elucidate the interactive function of the LC and VTA in ASD populations from the perspective of brain neuroimaging.…”
Section: Introductionmentioning
confidence: 99%